FUNGSI EKSTERNAL DAN KATEGORI FRASE NOMINA BAHASA MELAYU MANADO - Dongalemba, Rhode Margareth (Universitas Sam Ratulangi, 2018)
This research entitled â€œExternal Fuctions and Categories of Noun Phrase in Malay Manado Languageâ€. The analysis of this research focuses on describes the external functions and categories of noun phrase structure in Malay Manado language. This research contributes to the development of linguistics in the field of Syntactic especially External Fuctions and Categories of Noun Phrase in Malay Manado Language.The methodology that used in this research is desciptive method. The data is taken from interview natives people by using some social media like WhatsApp, Facebook, instagram, and as well as interview by face-to-face. All the data is primary which is the data obtained comes from first hand or original sources.The collected data are identified and analyzed in term of how the external function and categories of noun phrase is performed in the language by using Aarts & Aartsâ€™s theory (1982).The writer found 16 sentences data in Malay Manado language. The syntactic external function level is filled by subject, predicate, and adverb. The level of the external category, noun phrases attached to the subject function are 11 clauses, noun phrases that attach to the predicate function are 11 clauses, and noun phrases attached to the adverb are 4 clauses.Keyword : Syntactics, Function, Category, Malay Manado Language